Penerapan Kurikulum Merdeka Pada Kelas X SMAN 1 Lareh Sago Halaban Untuk Mewujudkan Tujuan Pendidikan Berarakter - Williya Yel Emiza; Amir Amril; Afnita Afnita (FKIP, Universitas Palangka Raya, 2023)
The research aims to analyze the implementation of the Merdeka Curriculum in the 10th grade of SMA Negeri 1 Lareh Sago Halaban in an effort to achieve educational goals with character. This study uses a qualitative descriptive approach. The research data was obtained through interviews with teachers and students, classroom observations, and analysis of curriculum-related documents. The research subjects consist of teachers and 10th-grade students at SMA Negeri 1 Lareh Sago Halaban. The researcher collected data through interviews with teachers involved in the implementation of the Merdeka Curriculum, classroom observations to observe the learning process, and analysis of documents related to the curriculum implementation. The results of the research show that the implementation of the Merdeka Curriculum in the 10th grade at SMA Negeri 1 Lareh Sago Halaban has provided a positive contribution in achieving character education goals. Teachers actively involve students in the learning process, give students the freedom to explore their potential, and promote the desired character values. Furthermore, students also benefit from the implementation of the Merdeka Curriculum. They feel more motivated and engaged in learning, have space for exploration and the development of creativity, and experience improvement in personal character formation. However, the research also identifies several challenges in the implementation of the Merdeka Curriculum. Factors such as limited resources and uneven understanding among teachers can affect the optimal implementation of this curriculum. To improve the effectiveness of the implementation of the Merdeka Curriculum, this research recommends training and mentoring for teachers to strengthen their understanding of this curriculum. Additionally, attention should be given to the development of resources that support the comprehensive implementation of the Merdeka Curriculum.